Adapting to threats: US counterterrorism strategy after 9/11 - Alexander, Kristian P. (2024)
The September 11, 2001, attacks highlighted significant US vulnerabilities and led to major counterterrorism reforms. Post-9/11, the US government implemented institutional changes, enhanced international cooperation, and expanded its use of technology and drone warfare. However, public fatigue from prolonged wars and shifting US focus towards geopolitical rivalries and domestic issues has reduced the centrality of counterterrorism in US policy over the last two decades.